Hydrology and ecology: how Natura 2000 and Military use can match - Nagels, Katia; Schneidewind, Uwe; El-Rawy, Mustafa; Batelaan, Okke; De Becker, Piet (Ecological Questions, 2015)
The military domain of Houthalen is a shooting area and also a protected Natura 2000 site, with an alternation of dunes, fens and heathlands. Already years ago, it was determined that the groundwater table is lowered by digging deep canals. Intensive consultation and study work (ecohydrological modeling) has shown that recovery is possible, taking into account the military use. Specific attention was paid to the accessibility through the fire roads and the water level in the fens. Recovery is started up, as well as a monitoring programme.